2006
DOI: 10.1080/07388550500508644
|View full text |Cite
|
Sign up to set email alerts
|

Composting: A Potentially Safe Process for Disposal of Genetically Modified Organisms

Abstract: The widespread use of genetically modified organisms (GMOs) may result in the release of GMOs into the environment. The potential risks regarding their use and implementation of disposal methods, especially the possibility of novel genes from GMOs being transferred to natural organisms, need to be evaluated and better understood. There is an increasingly accepted public view that GMO products introduced into the environment should be degradable and should disappear after a limited period of time. Due to the ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
6

Year Published

2007
2007
2023
2023

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 132 publications
0
7
0
6
Order By: Relevance
“…Numerous studies have shown that thermophilic composting destroys plant, human, and animal pathogens (Bollen 1993;Burge, Colacicco, and Cramer 1981;Pourcher et al 2005). Singh, Billingsley, and Ward (2006) reported that most bacterial pathogens are eliminated at 50 C within 3-15 days, while (Meynell and Meynell 1970). z Required holding time of 6 h exceeded.…”
Section: Fecal Coliformsmentioning
confidence: 97%
“…Numerous studies have shown that thermophilic composting destroys plant, human, and animal pathogens (Bollen 1993;Burge, Colacicco, and Cramer 1981;Pourcher et al 2005). Singh, Billingsley, and Ward (2006) reported that most bacterial pathogens are eliminated at 50 C within 3-15 days, while (Meynell and Meynell 1970). z Required holding time of 6 h exceeded.…”
Section: Fecal Coliformsmentioning
confidence: 97%
“…In general, release of DNA from different organisms occurs by cell lysis after death. However, some microorganisms possess active mechanisms for releasing large amounts of chromosomal or plasmid DNA which can reach concentrations that could support horizontal gene transfer by transformation (Singh et al 2006). Plant DNA enters the soil continuously, predominantly from the sloughing off of root cap cells, as a result of pathogen colonization of below-ground biomass, through pollen dispersal, and during crop residue decomposition.…”
Section: Fate Of Genetically Modified Organismsmentioning
confidence: 99%
“…Two replications for each type of compost mixture were conducted. The optimal moisture for efficient composting is generally 40-60% [10]. During the composting process, the humidity of the materials was maintained at a constant level of approx.…”
Section: Composting Experiments Set-upmentioning
confidence: 99%